The Influence of the Concept of Money and Monetary Policy in Islamic Economics - Moh Rizky Mulyadi; Moh Addul Gofar; Moh Aminulloh (Al-Fadilah: Islamic Economics Journal, 2025)
Growth in the economy is an illustration of how implemented government policies affect the economy. Monetary development is the pace of development framed from different financial areas which by implication depicts the degree of monetary development that happens . Kuznets and Sirojuzilam define economic growth as "a long-term increase in a country's ability to provide more and more goods to its population, this ability increases in accordance with technological progress and necessary institutional and ideological adjustments". To be able to achieve high but stable economic growth is not an easy job to do, this is like a two-sided coin, sometimes high but unstable economic growth is achieved. To achieve this, monetary policy is needed. Monetary policy aims to direct the macro economy to better and/or desirable conditions. These conditions are measured using main macro indicators such as maintaining good economic growth, controlled general price stability, and decreasing unemployment rates. The aim of monetary policy is to achieve economic stabilization. The success or failure of the objectives of monetary policy is influenced by two factors, first: whether or not the relationship between monetary policy and economic activity is strong,